2011
DOI: 10.2478/v10181-011-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey for bovine immunodeficiency virus in dairy cattle from Poland

Abstract: A seroprevalence study of bovine immunodeficiency virus (BIV) was undertaken on 1,541 serum samples from Holstein cattle from 23 herds, located in different geographical regions of Poland. The analysis was performed using ELISA, with recombinant Gag protein of BIV as antigen. The average BIV prevalence was 4.9% in individual cattle, while the percentage of herds harboring at least one seropositive animal, was 82.6%. To demonstrate the correlation of BIV and bovine leukemia virus infection, all sera were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In Poland, 1541 serum samples from Holstein cattle from 23 herds were analyzed using ELISA method. The average BIV prevalence was 4.9% in individual cattle while the percentage of herds harboring at least one seropositive animal, was 82.6% [29].…”
Section: Discussionmentioning
confidence: 94%
“…In Poland, 1541 serum samples from Holstein cattle from 23 herds were analyzed using ELISA method. The average BIV prevalence was 4.9% in individual cattle while the percentage of herds harboring at least one seropositive animal, was 82.6% [29].…”
Section: Discussionmentioning
confidence: 94%
“…The highest prevalence was noticed in Costa Rica (16) and the United States (28), while it was moderate in Japan (34), Pakistan (20) and Korea (6). Some reports also confirm BIV infections of cows in European countries: the Netherlands (17), Germany (22) and Poland (27) have been affected, but with lower seroprevalence. The most recent report on the occurrence of BIV in cattle comes from Mexico, showing a 28.94% prevalence (15).…”
Section: Introductionmentioning
confidence: 97%
“…The main pathologies associated with BIV are lymphadenopathy, lymphocytosis, non‐suppurative meningoencephalitis, progressive wasting, low milk production, low blastogenic lymphocytic response, bovine paraplegic syndrome and secondary infections derived from immunosuppression (Carpenter et al, ; Snider et al, ; Suarez, VanDerMaaten, Wood, & Whetstone, ; Van Der Maaten, Boothe, & Seger, ). There is controversy about the association or predisposition that may exist between the BIV and the bovine leukaemia virus (BLV; Brujeni, Poorbazargani, Nadin‐Davis, Tolooie, & Barjesteh, ; González et al, ; Rola, Kozaczynska, Pluta, & Kuzmak, ; Rola‐Łuszczak, Kozaczyńska, & Kuźmak, ). Recent findings (De Oliveira et al, ) in BIV sequences found within multicentric B‐cell lymphomas from BLV‐negative cows suggest their oncogenic potential.…”
Section: Introductionmentioning
confidence: 99%